Community based marketing strategies: A case study of a home-based microenterprise in expanding market - Nur Hidayatul Istiqomah; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Jurnal Bisnis Mahasiswa, 2025)
This study aims to explain how community participation contributes to the transformation of marketing strategies in Dana Berkah, a home-based batik microenterprise in Tuban. Employing a qualitative single-case study design, the research traces the how and why processes through in-depth interviews, direct observations, and analytical techniques including pattern matching, explanation building, time series analysis, and the logic model. The findings reveal that prior to joining the community, the enterprise experienced marketing isolation, limited visual documentation, restricted market reach, and passive promotional behavior. Participation in the MSME community generated substantial changes through the expansion of promotional channels, intensification of offline marketing activities, wider access to information, and the development of a stronger business identity. The community acted as a change mechanism by providing informal learning, information exchange, and emotional support that enhanced the owner’s confidence to adopt proactive marketing practices. These results highlight the role of community-based social capital in strengthening marketing capabilities among resource-constrained microenterprises. The study is limited by its single-case design, reliance on self-reported narratives, and the limited observation timeframe. Practically, the study offers a collaborative learning model applicable to batik microenterprises and other creative-sector MSMEs, and provides valuable insights for policymakers designing network-based empowerment strategies.